Arsis and thesis in ancient rhythmics and metrics: a new approach - Lynch, T (Cambridge University Press, 2016)
Since the beginning of modern investigations on ancient rhythmics, scholars have faced significant problems in interpreting the technical terminology employed by ancient rhythmicians, especially in relation to two of the most basic terms attested in the sources: ἄρσις and θέσις, which indicate the two fundamental components of a rhythmical foot.